2000
DOI: 10.1385/bter:75:1-3:79
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Levels and Alzheimer's Disease

Abstract: Concentrations of zinc in postmortem serum and four brain regions were measured by flame atomic absorption spectrometry and instrumental neutron activation analysis, respectively, in nine Alzheimer's disease (AD) and eight control subjects. A statistically significant elevation of zinc serum was observed in AD subjects (136.4+/-66.8 microg/dL) compared with age-matched control subjects (71.1+/-35.0 microg/dL). No significant differences were observed between AD and control zinc concentrations in the amygdala, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…These results were more in-line with the results of Deibel et al (1996), Panayi et al (2002) and Rulon et al (2000). Our measurements also showed a statistically significant 48% decrease in copper, a borderline significant 38% increase in iron and an insignificant 3% increase in zinc within the amygdala of AD patients.…”
Section: Literaturesupporting
confidence: 93%
See 2 more Smart Citations
“…These results were more in-line with the results of Deibel et al (1996), Panayi et al (2002) and Rulon et al (2000). Our measurements also showed a statistically significant 48% decrease in copper, a borderline significant 38% increase in iron and an insignificant 3% increase in zinc within the amygdala of AD patients.…”
Section: Literaturesupporting
confidence: 93%
“…Agreement is less pronounced with work of Deibel et al (1996) where no change in zinc concentration was found and iron was reported to increase, rather than decrease. The work of Panayi et al (2002) and Rulon et al (2000) also reported that zinc in the hippocampus was unchanged in averaged AD populations and is at odds with a study from Andrási et al (1995) that reported zinc is reduced by 59%.…”
Section: Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…2+ dyshomeostasis has been linked to a number of human pathologies including growth defects (Prasad, 2013), impaired immune function (Rink and Gabriel, 2000), diabetes (Jansen et al, 2009) and neurodegenerative diseases (Forsleff et al, 1999;Rulon et al, 2000;Lee et al, 2002;Vinceti et al, 2002). Regulation of cellular Zn 2+ levels involves controlling its influx, export and chelation.…”
Section: Cellular Znmentioning
confidence: 99%
“…Zinc content has been reported to be abnormally high in blood 165 and hippocampus 166 of AD patients. However, in the cerebrospinal fluid, zinc levels seem to be lowered in AD patients, 167 and globally in the brain, zinc levels have been reported to be unchanged 152 or reduced 168,169 in AD.…”
mentioning
confidence: 99%